Menumbuhkan Nilai-Nilai Anti Korupsi pada Anak untuk Membentuk Karakter Melalui â€œSemai Gamesâ€ Di MDTA Rabithatul Ulum Pekanbaru: ANTI-CORRUPTION EDUCATION FOR CHILDREN - Lailatul Izza (Psychopolytan : Jurnal Psikologi, 2019)
Growing anti-Corruption values is important in underlying children's character from an early age. This study aims to foster the values of Anti-Corruption to shape the character of the golden generation through "game seedlings" at the MDTA Rabithatul Ulum Pekanbaru. This research is qualitative research, namely research that describes the results of research with rational objective explanations. The subject of this study was Student MDTA Rabithatul Ulum, Pekanbaru. Methods of collecting data by participation observation, and documentation. Analysis techniques are descriptive qualitative with data reduction steps, data classification, data display and conclusion drawing. Based on the data and discussion, it can be concluded that growing anti-corruption values in the MDTA Rabuthatul Ulum in the form of learning devices that use card games, game maps, media use manuals. The results of the design of learning media, which were named "seedlings for Games", made it very easy for students to more quickly understand the values of anti-corruption in the form of daily behavior at home and school. This behavior change was seen in the independence of Saturday Clean activities, savings for consumption in schools, increased charity carried out at Friday Shadaqoh, discipline which was seen in the decline in the number of late students, as well as the self-confidence seen in repetition activities and competitions between schools.